Analysis of the Role of PPAT as a Shield in Illegal Property Transactions to Intercept the Land Mafia - Hilbertus Sumplisius M. Wau; T. Keizerina Devi Azwar (Jurnal Ilmu Kenotariatan, 2023)
Illegal property transactions conducted by land mafias pose a serious threat to property transactions and land ownership. In this context, the role of the Land Deed Official (PPAT) plays a crucial role in preventing such illegal practices. The objective of this research is to analyze the role of PPAT as a shield in illegal property transactions carried out by land mafias. This study adopts a descriptive-analytical normative legal research approach, with secondary data as the primary source. Data collection techniques involve literature review, and data analysis focuses on identifying the modus operandi of land mafias, the role of PPAT in preventing illegal transactions, and their impact on society. The findings reveal that PPAT has the responsibility to verify documents, communicate with relevant institutions, reject suspicious transactions, and collaborate with law enforcement agencies. PPAT also plays a crucial role in educating the public and raising awareness about the dangers of land mafias. In conclusion, the role of PPAT in preventing illegal property transactions by land mafias is of utmost importance. Through stringent oversight, collaboration with relevant institutions, rejection of suspicious transactions, and public education, PPAT can act as the forefront in combating land mafia practices. By fully understanding their role, PPAT can protect the public, uphold property justice, and prevent the negative impacts caused by these illegal practices. KEYWORDS: Illegal, Land Mafia, PPAT, Property.